Impacts of COVID-19 pandemic prevention measures to the palliative care in Taiwan - Wu, Meng-Ping; Hsiaog, Sheng-huang; Huang, Tsun-Cheng; Chu, Da-Chen; Liu, Chieh-Yu (Frontiers in Public Health, 2024)
Background: Prevention measures for palliative care and the provision of discharge planning services for inpatients in Taiwan before and during the COVID-19 pandemic had not been investigated. This study was aimed to investigate the factors associated with heightened palliative care needs and increased mortality rates. Methods: This research adopts a retrospective case-control study design. The investigation encompasses patients admitted before the pandemic (from January 1, 2019, to May 31, 2019) and during the COVID-19 pandemic (from January 1, 2020, to May 31, 2020). The case group consisted of 231 end-of-life inpatients during the pandemic, control group was composed of the pool of inpatients with pre-pandemic and matched with cases by sex and age in a 1:1 ratio. Results: The results showed that the prevalence of respiratory failure symptoms (p=0.004), residing in long-term care facilities (p=0.017), palliative care needs assessment scores (p=0.010), as well as the provision of guidance for nasogastric tube feeding (p=0.002), steam inhalation (p=0.003), turning and positioning (p<0.001), percussion (p<0.001), passive range of motion (p<0.001), and blood pressure measurement (p<0.001). Furthermore, the assessment of the necessity for assistive devices, including hospital beds, also exhibited statistically significant variations (p<0.001). Further investigation of the factors associated with high palliative care needs and the risk of mortality for both the case and control groups. Risk factors for high palliative care needs encompassed assessments of daily activities of living, the presence of pressure ulcers, and the receipt of guidance for ambulation. Risk factors for mortality encompassed age, a diagnosis of cancer, palliative care needs assessment scores, and the provision of guidance for disease awareness. Conclusions: This research highlights the heightened risk of COVID-19 infection among end-of-life inpatients during the COVID-19 pandemic. The findings of this study may advance care planning to alleviate avoidable suffering. To meet the needs of inpatients during pandemic, healthcare professionals should undergo comprehensive palliative care training and receive policy support.